Neurodevelopmental Outcomes after Congenital Heart Disease Surgery in Infancy: A 2-Year Serial Follow-Up - Kyeong Joo Song; Min Gi Kim; Eun Jae Ko; In Young Sung (MDPI AG, 2021)
Background: The aim of this study is to assess the neurodevelopmental status of infant patients who underwent cardiac surgery in infancy and to investigate the factors affecting the neurodevelopmental status. Methods: This retrospective study included 108 patients who underwent cardiac surgery before the age of one. We used the Bayley Scales of Infant Development II to evaluate the neurodevelopmental status. All patients were analyzed according to the presence of the syndrome. Patients without the syndrome were analyzed according to the presence of brain lesions. Results: The mean mental developmental index (MDI) and the mean psychomotor developmental index (PDI) were 76.11 ± 20.17 and 65.95 ± 18.34, respectively, in the first evaluation, and 73.98 ± 22.53 and 69.48 ± 20.86, respectively, in the second evaluation. In the subgroup analysis, no significant difference was observed between the first evaluation and the second evaluation. Conclusions: No significant difference was observed in the degree of development of the patients in the two evaluation periods. Although the presence of syndrome, brain lesion, or gestational age affected the degree of developmental delay, more than half of the patients had developmental delay in the two evaluation periods in any of the subgroup. Therefore, the necessity of early screening and early rehabilitation intervention is emphasized.